Discovering a population of Tylototriton verrucosus (Caudata: Salamandridae) from Thailand: Implications for conservation - Porrawee Pomchote (2020)
© 2020 by Chulalongkorn University. The Asian newt genus Tylototriton, is the only urodelan genus currently recorded in Thailand. For a long time in the past, T. verrucosus was the sole known urodelan species found in Thailand, but was recently shown to be comprised of three cryptic species, T. uyenoi, T. anguliceps, and T. panhai. However, in our molecular study, the newts from Doi Chang, Chiang Rai Province were different from these three recognized Tylototriton species, and nested within the clade of T. verrucosus from China. They also had morphological traits similar to T. verrucosus. These results lead to the confirmation of the existence of T. verrucosus in Thailand. The habitats of T. verrucosus need to be protected by future conservation plans.